EasyHarvest: a digital tool for smart management of agricultural machinery and paddy and residue logistics in Philippines and Vietnam - CGIAR Research Program on Rice (2021)
'- The EasyHarvest is successful piloted for laser land leveling application in the Philippines - The EasyHarvest is being tested for optimized wet paddy logistics of Loc Troi Group in Vietnam